Alkali metal-containing oxide, positive electrode active material, electrode, and battery
By using alkali metal oxides containing specific constituent structures as the positive electrode material of the battery, the problem of insufficient charge and discharge capacity of spinel-type oxides is solved, and the charging and discharge capacity and Coulomb efficiency are improved, providing excellent battery performance.
Patent Information
- Application Number
- CN202380041942.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-04
- Filing Date
- 2023-05-19
- Publication Date
- 2025-01-10
AI Technical Summary
There is room for improvement in the charge and discharge capacity of spinel-containing alkali metal oxides, and the prior art is difficult to effectively improve its performance.
An alkali metal-containing oxide with a specific composition structure is adopted, the general formula is AxM'aM"bZcO4-eXd, where A is an alkali metal element, M' is Ti, Cr, Mn, Fe, Co, Ni, Cu and other elements, M " is Si, P, S, Ge, V and other elements, Z is the 2nd to 16th group of the periodic table. The half-value amplitude is 0.5 to 45° from the range of 2θ, measured from 2θ. The peak of 5° is used as the positive electrode material in the battery, and the electrochemical reaction is carried out in combination with the lithium salt electrolyte.
The charging and discharge capacity and Coulomb efficiency of alkali metal oxides are significantly improved, providing excellent battery performance, including efficient lithium ion embedding capabilities and stable battery performance.
Smart Images

Figure CN119301072A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an alkali metal oxide, a positive electrode active material, an electrode and a battery. Background Art
[0002] It is known that there are secondary batteries that are charged and discharged by the movement of alkali metal ions between the positive electrode and the negative electrode. Among such secondary batteries, lithium ion secondary batteries are representative and have been put into practical use as small power sources for mobile phones and laptop computers, and can be used as large power sources such as power sources for automobiles such as electric vehicles and hybrid vehicles or power sources for distributed power storage, so their demand is increasing.
[0003] As the positive electrode active material of the above-mentioned secondary battery, an alkali metal oxide having a spinel crystal structure is known. Such an alkali metal oxide, for example, has 32 oxide ions in one unit cell, such as LiMn2O4, with alkali metal ions occupying 8 tetrahedral sites and transition metal ions occupying 16 octahedral sites. In addition, there are also known alkali metal oxides having an alkali metal excess composition, such as a composition ratio of more than 1 alkali metal element per 4 oxygens and a composition ratio of less than 2 transition metal elements per 4 oxygens (Patent Documents 1 to 6).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 07-122299
[0007] Patent Document 2: Japanese Patent Publication No. 2000-500280
[0008] Patent Document 3: Japanese Patent Application Publication No. 2000-063123
[0009] Patent Document 4: Chinese Patent Application Publication No. 102163716
[0010] Patent Document 5: Chinese Patent Application Publication No. 103594700
[0011] Patent Document 6: Japanese Patent Application No. 2014-525667 Summary of the invention
[0012] Problems to be solved by the invention
[0013] Among them, spinel-type alkali metal-containing oxides have room for improvement in charge and discharge capacity.
[0014] The present disclosure has been made in view of the above circumstances, and an object of the present disclosure is to provide an alkali metal oxide having excellent charge and discharge capacity, and an electrode and a battery containing such an alkali metal oxide.
[0015] Means for solving problems
[0016] The alkali metal oxide disclosed in the present invention has a spinel structure and a composition represented by the following general formula (1). In the X-ray diffraction pattern obtained by measuring the alkali metal oxide using CuKα rays at 25°C, a peak with a half-value width of 0.5 to 5° in 2θ is observed in the range of 40 to 45° in 2θ.
[0017] A x M' a M” b Z c O 4-e X d (1)
[0018] (In formula (1), 1.1<x≤2.8, 0.8≤a≤1.9, 0.05<b≤0.6, 1.0≤a+b<2.0, 0≤c<0.2, 0≤d<1.0, 0≤e<1.0,
[0019] A is an alkali metal element,
[0020] M' is at least one element selected from the group consisting of Ti, Cr, Mn, Fe, Co, Ni and Cu,
[0021] M" is at least one selected from the group consisting of Si, P, S, Ge and V,
[0022] Z is an element of Group 2 to Group 16 of the periodic table other than oxygen, M' and M",
[0023] X is a halogen element.)
[0024] For the above-mentioned alkali metal oxide, an electrochemical cell is prepared, which includes an electrode containing the alkali metal oxide, a counter electrode of lithium metal, and an electrolyte containing a lithium salt disposed between the electrode and the counter electrode, and Li / Li + When the battery is charged to 4.8 V and then discharged to 1.5 V, x in the general formula (1) is in the range of 2.2 to 2.8.
[0025] In the above general formula (1), A may contain Li.
[0026] In the above general formula (1), M" may contain V.
[0027] In the above general formula (1), 1.1<x≤2.0 may be satisfied.
[0028] The electrode of the present disclosure includes the above-mentioned alkali metal-containing oxide.
[0029] The nonaqueous secondary battery of the present disclosure includes the above-mentioned electrode as a positive electrode and a negative electrode containing lithium.
[0030] Effects of the Invention
[0031] According to the present disclosure, it is possible to provide an alkali metal oxide having excellent charge-discharge capacity and coulombic efficiency, and an electrode and a battery containing such an alkali metal oxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is the X-ray diffraction pattern of the lithium-containing oxide of Examples 1-4.
[0033] Figure 2 It is the X-ray diffraction pattern of the lithium-containing oxide of Examples 5-8.
[0034] Figure 3 It is the X-ray diffraction diagram of the lithium-containing oxide of Examples 9 and 10 and Comparative Examples 1 to 3.
[0035] Figure 4 This is a graph showing the first charge and discharge curves of Comparative Example 1 and Examples 1 and 3 to 6.
[0036] Figure 5 This is a graph showing the first charge and discharge curves of Comparative Example 1 and Examples 2, 7, and 8.
[0037] Figure 6 This is a graph showing the first charge and discharge curves of Comparative Example 1 and Examples 9 and 10.
[0038] Figure 7 This is a graph showing the first charge and discharge curves of Comparative Examples 1 to 3.
[0039] Figure 8 The composition ratio x of lithium (i.e., the composition formula Li x Mn 1.4 V 0.3 A graph with the x in O4) as the horizontal axis and the battery voltage as the vertical axis.
[0040] Fig. 9 This is a diagram showing an electron diffraction image of the sample of Example 5.
[0041] Fig.10 This is a diagram showing a dark field observation image of the sample of Example 5 using a transmission microscope. DETAILED DESCRIPTION
[0042] The alkali metal oxide of this embodiment has a spinel structure and has a composition represented by the following general formula (1). In the X-ray diffraction pattern obtained by measuring the alkali metal oxide using CuKα rays at 25°C, a peak with a half-value width of 0.5 to 5° in 2θ is observed in the range of 40 to 45° in 2θ.
[0043] A x M' a M” b Z c O 4-e X d (1)
[0044] (In formula (1), 1.1<x≤2.8, 0.8≤a≤1.9, 0.05<b≤0.6, 1.0≤a+b<2.0, 0≤c<0.2, 0≤d<1.0, 0≤e<1.0,
[0045] A is an alkali metal element,
[0046] M' is at least one element selected from the group consisting of Ti, Cr, Mn, Fe, Co, Ni and Cu,
[0047] M" is at least one selected from the group consisting of Si, P, S, Ge and V,
[0048] Z is an element of Group 2 to Group 16 of the periodic table other than oxygen, M' and M",
[0049] X is a halogen element.)
[0050] A is not particularly limited as long as it is an alkali metal element, but may include at least one selected from the group consisting of Li, Na, K, Rb and Cs, may include at least one selected from the group consisting of Li, Na and K, may include at least one of Li and Na, and may include Li.
[0051] The content of one alkali metal in the total amount of alkali metals contained in the alkali metal-containing oxide of the present embodiment may be 90 mol% or more, 95 mol% or more, 98 mol% or more, 99 mol% or more, 99.9 mol% or more, or may substantially contain only one alkali metal (i.e., the content of alkali metals other than the one alkali metal is substantially 0 mol%). The one alkali metal may be Li, Na or K, Li or Na, or Li. In the case where the alkali metal-containing oxide mainly contains Li (for example, in the case where the content of one alkali metal in the total amount of alkali metals contained in the alkali metal-containing oxide is 80 mol% or more, etc.), there is a tendency to observe a peak with a half-value width of 0.5 to 5° in 2θ in the range of 43 to 45° in 2θ in the X-ray diffraction pattern.
[0052] In formula (1), x may be greater than 1.1 and less than 2, may be 1.13 to 2.75, may be 1.15 to 2.7, may be 1.2 to 2.6, may be 1.25 to 2.5. In addition, x may be 1.13 to 2.1, may be 1.15 to 2.0, may be 1.2 to 1.95, may be 1.25 to 1.9.
[0053] M′ may include at least one element selected from the group consisting of Ti, Cr, Mn, Fe, Co, Ni, and Cu, may include at least one of Cr, Mn, and Ni, may include at least one of Mn and Ni, and may include Mn.
[0054] M" may contain at least one element selected from the group consisting of Si, P, S, Ge and V, may contain at least one of P and V, and may contain V. M" may contain V or contain V and P.
[0055] a can be 0.9 to 1.9, 1.0 to 1.85, 1.0 to 1.7, or 1.0 to 1.6. b can be 0.06 to 0.58, 0.08 to 0.55, or 0.1 to 0.5. b can be 0.15 to 0.55, or 0.2 to 0.5.
[0056] a+b can be 1.2 to 1.95, or 1.5 to 1.93.
[0057] Z is an element of Group 2 to Group 16 of the periodic table other than oxygen, M′ and M″, and examples thereof include Al, Mg, Ca, Zr, Nb, Mo, Ru, W, Sn and the like.
[0058] c may be 0.1 or less, 0.05 or less, 0.01 or less, or substantially 0.
[0059] X may include at least one element selected from the group consisting of F, Cl, Br, and I, may include at least one of F and Cl, and may include F.
[0060] d may be less than 0.8, less than 0.6, less than 0.4, less than 0.2, less than 0.05, or less than 0.01. d may be greater than or equal to 0.001, or may be 0. In addition, d may be between 0.001 and 0.8, between 0.001 and 0.6, or between 0.001 and 0.2. e may be less than 0.8, less than 0.6, less than 0.4, less than 0.2, less than 0.05, less than 0.01, or may be 0. e may be greater than or equal to 0.001. In addition, e may be between 0.001 and 0.8, between 0.001 and 0.6, or between 0.001 and 0.2.
[0061] The half-value width of the X-ray diffraction peak observed in the above-mentioned range of 40 to 45° may be 0.7 to 4.5°, 0.9 to 4.0°, 1.0 to 3.8°, or 1.28 to 3.5°. The half-value width of the X-ray diffraction peak observed in the above-mentioned range of 43 to 45° may be 0.7 to 4.5°, 0.9 to 4.0°, 1.0 to 3.8°, or 1.28 to 3.5°.
[0062] In the alkali metal-containing oxide of the present embodiment, a peak having a half-value width of 0.5 to 8° in 2θ may be observed in the above X-ray diffraction pattern within the range of 63 to 66° in 2θ. The half-value width of the peak may be 1.0 to 7.5°.
[0063] The alkali metal oxide of the present embodiment may also have an amorphous phase while having a crystalline phase. The crystalline phase may be dispersed in the amorphous phase. The presence of the amorphous phase tends to improve the diffusion of lithium ions in the material. The alkali metal oxide of the present embodiment may also have a crystalline phase (crystallites) having an average particle size of 1 to 30 nm in terms of equivalent circle diameter. The average particle size of the crystalline phase (crystallites) may be 1 to 20 nm in terms of equivalent circle diameter, or 1 to 15 nm. Among them, the amorphous phase can be confirmed by observation using a transmission electron microscope (TEM).
[0064] The alkali metal-containing oxide of the present embodiment may also contain 8 to 15% by mass of Li, 32 to 57% by mass of at least one element M' selected from the group consisting of Ti, Cr, Mn, Fe, Co, Ni and Cu, and 3 to 30% by mass of at least one element M", selected from the group consisting of Si, P, S, Ge and V. In the X-ray diffraction pattern obtained by measuring using CuKα rays at 25°C, a peak pattern belonging to a spinel structure is observed, and a peak with a half-value width of 0.5 to 5° is observed in the range of 40 to 45° in terms of 2θ. The alkali metal-containing oxide may also contain an element Z from Group 2 to Group 16 of the periodic table other than oxygen, M' and M". Specifically, the element Z can be exemplified as Z in the above-mentioned general formula (1). The content of Z can be 20% by mass or less, 10% by mass or less, 5% by mass or less, 1% by mass or less, or substantially 0% by mass, relative to the total amount of the alkali metal-containing oxide. In addition, the alkali metal oxide may also contain halogen elements, and as halogen elements, elements exemplified as X of the general formula (1) may be listed. The content of the halogen elements may be less than 20 mass %, less than 10 mass %, less than 5 mass %, less than 1 mass %, or substantially 0 mass % relative to the total amount of the alkali metal oxide. The alkali metal oxide may be single-phase or multi-phase, or may be observed to have peaks other than the peaks belonging to the spinel structure when performing an X-ray diffraction test. The alkali metal oxide may also have an amorphous phase while having a crystalline phase (crystal).
[0065] There are no particular restrictions on the method for producing the alkali metal-containing oxide, but a method of mechanochemically mixing a spinel oxide containing Li and M' and an alkali metal salt containing M" using a ball mill can be cited. As the spinel oxide, for example, in the case of lithium-containing oxides, LiMnTiO4, LiCrMnO4, LiMn2O4, LiFeMnO4, LiCoMnO4, LiNi 0.5 Mn 1.5 O4、LiCu 0.5 Mn 1.5 O4. As lithium salts, Li3VO4, Li4SiO4, Li2SiO3, Li3P 0.5 V 0.5O4, Li2GeO4, Li2SO4, etc. In addition, as raw materials, alkali metal oxides such as Li2O, oxides of M' or M" such as V2O5, GeO2, SiO2, etc. can also be used as raw materials. The raw materials are not limited to the above, as long as the compound containing at least one of Li, M' and M" and oxygen is mixed in a manner to achieve the target composition. There are no special restrictions on the conditions of the ball mill, and the rotation speed can be 100-700 rpm, and the mixing time can be 0.5-72 hours, or 10-60 hours. In addition, the mixing time can also be 20-72 hours, or 30-60 hours. In addition, when X in the general formula (1) is introduced, an alkali metal salt of X can also be used as a raw material.
[0066] The alkali metal oxide of the present embodiment can be used as a material for a battery (lithium ion battery, sodium ion battery, etc.). That is, the battery of the present embodiment includes the above-mentioned alkali metal oxide. The battery can also be a primary battery or a secondary battery. In addition, the battery can be a non-aqueous secondary battery. In the battery, the above-mentioned alkali metal oxide can be included in the electrode.
[0067] The battery of this embodiment includes a positive electrode, a negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode.
[0068] The positive electrode of this embodiment includes a current collector and a positive electrode mixture supported on the current collector. The positive electrode mixture may form a positive electrode mixture layer on the current collector.
[0069] The positive electrode mixture contains the above-mentioned alkali metal-containing oxide, and may contain a conductive material (conductive aid), a binder, etc. as necessary. That is, the above-mentioned alkali metal-containing oxide may be contained in the positive electrode active material.
[0070] As the conductive material, carbon materials such as natural graphite, artificial graphite, coke, carbon black, acetylene black, etc. can be listed. As the binder, thermoplastic resins can be listed, specifically, fluororesins such as polyvinylidene fluoride (hereinafter, also referred to as "PVDF"), polytetrafluoroethylene, tetrafluoroethylene, hexafluoropropylene, vinylidene fluoride copolymers, hexafluoropropylene, vinylidene fluoride copolymers, tetrafluoroethylene, perfluorovinyl ether copolymers, etc. can be listed; and polyolefin resins such as polyethylene and polypropylene, etc. As the collector, Al, Ni, stainless steel, etc. can be used.
[0071] As a method for carrying a positive electrode mixture on a current collector, there can be listed a method of press molding, a method of pasting the electrode mixture using an organic solvent, etc., applying it to the current collector, and pressing it after drying to fix it, etc. In the case of pasting, for example, a slurry containing the above-mentioned positive electrode active material, a conductive material, a binder and an organic solvent is prepared. As an organic solvent, there can be listed amines such as N,N-dimethylaminopropylamine and diethyltriamine; ethers such as ethylene oxide and tetrahydrofuran; ketones such as methyl ethyl ketone; esters such as methyl acetate; aprotic polar solvents such as dimethylacetamide and N-methyl-2-pyrrolidone, etc. As a method for coating the electrode mixture on the current collector, for example, there can be listed a slit die extrusion coating method, a screen coating method, a curtain coating method, a doctor blade coating method, a gravure coating method, an electrostatic spray, etc.
[0072] The negative electrode of the battery is not particularly limited, and may be a negative electrode containing a negative electrode active material and, as required, a conductive aid, a binder, and the like. For example, as a negative electrode active material for a lithium ion battery, single substances of elements such as Li, Si, P, Sn, Si-Mn, Si-Co, Si-Ni, In, Au, and alloys or composites containing these elements, carbon materials such as graphite, and materials in which lithium ions are embedded between the layers of the carbon material, etc., may be listed. In the case of a negative electrode of a sodium ion battery, a substance obtained by replacing the Li of a substance listed as a negative electrode material for a lithium ion battery with Na may be used as a negative electrode material.
[0073] The electrolyte of the battery is not particularly limited, and an electrolyte obtained by dissolving an alkali metal salt in an organic solvent can be used. In addition, the electrolyte can also be a solid electrolyte. As the alkali metal salt, iodide salts, tetrafluoroborate, hexafluorophosphate, bis(fluorosulfonyl)imide salts, bis(trifluoromethylsulfonyl)imide salts, etc. can be listed.
[0074] The organic solvent contained in the electrolyte is not particularly limited, and non-aqueous solvents, for example, cyclic carbonate esters such as ethylene carbonate (EC) or propylene carbonate (PC), straight-chain carbonate esters such as dimethyl carbonate (DMC), diethyl carbonate (DEC), or ethyl methyl carbonate (EMC), or sultones, etc. can be listed. The solvent can also be used alone or in combination of two or more.
[0075] The alkali metal oxide of the present embodiment has excellent alkali metal ion embedding ability. Therefore, the alkali metal oxide of the present embodiment is used to prepare an electrochemical cell including an electrode including the alkali metal oxide, a counter electrode of lithium metal, and an electrolyte solution containing a lithium salt disposed between the electrode and the counter electrode, and the Li / Li +When the battery is charged to 4.8 V (initial charge) and then discharged to 1.5 V, x in general formula (1) may be in the range of 2.2 to 2.8. After the initial charge and discharge, x may be 2.25 to 2.7, 2.3 to 2.6, or 2.35 to 2.55.
[0076] The positive electrode active material of this embodiment may also be: it comprises a composite oxide containing an alkali metal element, an element M' and an element M", wherein the composite oxide comprises 8 to 27% by mass of an alkali metal element, 26 to 57% by mass of at least one element M' selected from the group consisting of Ti, Cr, Mn, Fe, Co, Ni and Cu, and 2 to 30% by mass of at least one element M' selected from the group consisting of Si, P, S, Ge and V. In the X-ray diffraction pattern obtained by measuring the positive electrode active material at 25°C using CuKα rays, a peak pattern of a spinel structure originating from the composite oxide is observed, and a peak with a half-value width of 0.5 to 5° is observed in the range of 40 to 45° in terms of 2θ. The composite oxide contained in the positive electrode active material may contain the above-mentioned alkali metal-containing oxide. The positive electrode active material may also have a crystalline phase (microcrystal) and an amorphous phase of the composite oxide.
[0077] The present disclosure includes the following exemplary embodiments.
[0078] Implementation Method 1
[0079] An alkali metal oxide. The alkali metal oxide has a spinel structure and has a composition represented by the following general formula (1):
[0080] In the X-ray diffraction pattern of the alkali metal-containing oxide measured at 25°C using CuKα rays, a peak having a half-value width of 0.5 to 5° in 2θ is observed in the range of 40 to 45° in 2θ.
[0081] A x M' a M” b Z c O 4-e X d (1)
[0082] (In formula (1), 1.1<x≤2.8, 0.8≤a<1.9, 0.05<b≤0.6, 1.0≤a+b<2.0, 0≤c<0.2, 0≤d<1.0, 0≤e<1.0,
[0083] A is an alkali metal element,
[0084] M' is at least one element selected from the group consisting of Ti, Cr, Mn, Fe, Co, Ni and Cu,
[0085] M" is at least one selected from the group consisting of Si, P, S, Ge and V,
[0086] Z is an element of Group 2 to Group 16 of the periodic table other than oxygen, M' and M",
[0087] X is a halogen element.)
[0088] Implementation Method 2
[0089] According to the alkali metal-containing oxide of embodiment 1, wherein the alkali metal-containing oxide is prepared in an electrochemical cell having an electrode including the alkali metal-containing oxide, a counter electrode of lithium metal, and an electrolyte solution containing a lithium salt disposed between the electrode and the counter electrode, and Li / Li + When the electrochemical battery is charged to 4.8 V and then discharged to 1.5 V, x in the general formula (1) is in the range of 2.2 to 2.8.
[0090] Implementation 3
[0091] The alkali metal-containing oxide according to Embodiment 1 or 2, wherein, in the above general formula (1), A contains Li.
[0092] Implementation 4
[0093] The alkali metal-containing oxide according to any one of Embodiments 1 to 3, wherein in the general formula (1), M″ contains V.
[0094] Implementation method 5
[0095] The alkali metal-containing oxide according to any one of Embodiments 1 to 4, wherein in the general formula (1), 1.1<x≤2.0.
[0096] Implementation 6
[0097] The alkali metal-containing oxide according to any one of Embodiments 1 to 5 has an amorphous phase.
[0098] Implementation 7
[0099] An electrode comprising the alkali metal-containing oxide according to any one of Embodiments 1 to 6.
[0100] Implementation 8
[0101] A battery comprising the electrode according to Embodiment 7 as a positive electrode and a negative electrode containing lithium.
[0102] Implementation method 9
[0103] A positive electrode active material, comprising a composite oxide containing an alkali metal element, an element M' and an element M", wherein:
[0104] The positive electrode active material contains 8 to 15 mass % of alkali metal elements, 32 to 57 mass % of at least one element M' selected from the group consisting of Ti, Cr, Mn, Fe, Co, Ni and Cu, and 3 to 30 mass % of at least one element M", selected from the group consisting of Si, P, S, Ge and V. In the X-ray diffraction pattern obtained by measuring the positive electrode active material using CuKα rays at 25°C, a peak pattern of a spinel structure originating from the above-mentioned composite oxide was observed, and a peak with a half-value width of 0.5 to 5° was observed in the range of 40 to 45° in 2θ.
[0105] Embodiment 10
[0106] According to the positive electrode active material of the ninth embodiment, it has an amorphous phase.
[0107] Implementation 11
[0108] An alkali metal-containing oxide having a crystalline phase and an amorphous phase containing a spinel structure and having a composition represented by the following general formula (1),
[0109] In the X-ray diffraction pattern of the alkali metal-containing oxide measured at 25°C using CuKα rays, a peak having a half-value width of 0.5 to 5° in 2θ is observed in the range of 40 to 45° in 2θ.
[0110] AxM'aM"bZcO4-eXd(1)
[0111] (In formula (1), 1.1<x≤2.8, 0.8≤a<1.9, 0.05<b≤0.6, 1.0≤a+b<2.0, 0≤c<0.2, 0≤d<1.0, 0≤e<1.0,
[0112] A is an alkali metal element,
[0113] M' is at least one element selected from the group consisting of Ti, Cr, Mn, Fe, Co, Ni and Cu,
[0114] M" is at least one selected from the group consisting of Si, P, S, Ge and V,
[0115] Z is an element of Group 2 to Group 16 of the periodic table other than oxygen, M' and M",
[0116] X is a halogen element.)
[0117] Example
[0118] (Example 1)
[0119] LiMn2O4 powder and Li3VO4 powder as raw materials are produced as follows.
[0120] First, lithium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and manganese (IV) oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed in a molar ratio of 1:4, and the mixture was calcined at 800°C for 18 hours in air to obtain LiMn2O4 powder. In addition, lithium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and vanadium (V) oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed in a molar ratio of 3:1, and the mixture was calcined at 650°C for 12 hours in air to obtain Li3VO4 powder.
[0121] The obtained LiMn2O4 powder and Li3VO4 powder were mixed at a molar ratio of 0.9:0.1, and zirconia balls with a diameter of 4 mm and the mixed powder were introduced into a zirconia ball mill container in a mass ratio of 65:1. The ball mill container was introduced into a planetary ball mill device (PM200 manufactured by Retsch) and ball milled at a rotation speed of 500 rpm for 48 hours to obtain a lithium-containing oxide.
[0122] (Examples 2 to 6 and Comparative Example 3)
[0123] As shown in Table 1, a lithium-containing oxide was produced in the same manner as in Example 1 except that the blending amounts and / or mixing time of the LiMn 2 O 4 powder and the Li 3 VO 4 powder as raw materials were changed.
[0124] (Example 7)
[0125] As raw materials, LiNi 0.5 Mn 1.5 A lithium-containing oxide was produced in the same manner as in Example 1 except that the O4 powder and the Li3VO4 powder were used in a molar ratio of 0.8:0.2.
[0126] It should be noted that LiNi 0.5 Mn 1.5 O4 powder is obtained by the following method: lithium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), nickel (II) oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and manganese (IV) oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) are weighed in a molar ratio of 1:1:3, mixed with ethanol and zirconium oxide balls with a diameter of 8 mm using a wet ball mill, and the filtered and dried mixed powder is calcined in the atmosphere at 600°C for 15 hours.
[0127] (Example 8)
[0128] As raw materials, LiMn2O4 powder and Li3V 0.5 P 0.5 O4 powder were used in a molar ratio of 0.8:0.2. Except for this, a lithium-containing oxide was produced in the same manner as in Example 1.
[0129] It should be noted that the Li3V 0.5 P 0.5 O4 powder was obtained by the following method: Lithium carbonate (manufactured by Fujifilm Wako Pure Chemical Corporation), diammonium hydrogen phosphate (manufactured by Fujifilm Wako Pure Chemical Corporation), and vanadium(V) oxide (manufactured by Fujifilm Wako Pure Chemical Corporation) were mixed in a molar ratio of 6:2:1 and fired in the atmosphere at 800 °C for 10 hours.
[0130] (Examples 9 and 10)
[0131] As raw materials, LiCrMnO4 powder and Li3VO4 powder were used in the molar ratios shown in Table 1. Except for this, a lithium-containing oxide was produced in the same manner as in Example 1.
[0132] It should be noted that LiCrMnO4 was obtained by the following method: Lithium carbonate (manufactured by Fujifilm Wako Pure Chemical Corporation), chromium(III) oxide (manufactured by Fujifilm Wako Pure Chemical Corporation), and manganese(III) oxide (manufactured by Fujifilm Wako Pure Chemical Corporation) were mixed in a molar ratio of 1:1:1, fired in air at 800 °C for 6 hours, and further fired in air at 900 °C for 12 hours.
[0133] (Comparative Example 1)
[0134] A lithium-containing oxide was produced in the same manner as in Example 1, except that only the LiMn2O4 powder was ball-milled.
[0135] (Comparative Example 2)
[0136] The LiMn2O4 powder of the raw materials produced in Example 1 was directly used.
[0137] <X-ray Diffraction>
[0138] Powder X-ray diffraction measurement was performed on each lithium-containing oxide of the embodiment and comparative example using a powder X-ray diffraction measuring apparatus (Ultima IV manufactured by Rigaku Co., Ltd.). The measurement was performed at room temperature (25°C). The above-mentioned lithium-containing oxide was filled in the recess of the glass plate, and the glass plate carrying the sample was sealed in an airtight sample stand with a beryllium window to avoid air and moisture, and the measurement was performed without exposure to the atmosphere. A CuKα ray source was used with an output power of 40 kV and 40 mA, and the diffraction angle range of 2θ = 10° to 90° was measured at a step of 0.02° and a speed of 2° / min. The peak position and half-value width of the peak observed at 40 to 45° (2θ) are shown in Tables 1 and 2. Figure 1 It is the X-ray diffraction pattern of the lithium-containing oxide of Examples 1-4. Figure 2 It is the X-ray diffraction pattern of the lithium-containing oxide of Examples 5-8. Figure 3 is the X-ray diffraction pattern of the lithium-containing oxides of Examples 9 and 10 and Comparative Examples 1 to 3. Figures 1 to 3 As can be seen, the lithium-containing oxides of Examples 1 to 10 show the same diffraction patterns as that of Comparative Example 2.
[0139] [Table 1]
[0140]
[0141] [Table 2]
[0142]
[0143] <Charge and discharge test>
[0144] (1) Preparation of positive electrode
[0145] The lithium-containing oxide (positive electrode active material) of Examples 1 to 10 and Comparative Examples 1 and 3, acetylene black (trade name: HS-100, manufactured by Denka Co., Ltd.) as a conductive material, and polytetrafluoroethylene (PTFE, product number: 6-J, Chemours-Mitsui Fluoroproducts Co., Ltd.) as a binder are weighed in such a way that the composition becomes positive electrode active material: conductive material: binder = 70:20:10 (mass ratio). First, the positive electrode active material and the conductive material are thoroughly mixed with an agate mortar, and the binder is added and further mixed. Weigh 7 mg of the mixture and draw it into a circle on the mortar. The drawn mixture is crimped to an aluminum mesh (100 mesh, manufactured by The Nilaco Co., Ltd.) with a thickness of 110 μm as a collector to obtain a positive electrode containing a positive electrode active material.
[0146] For Comparative Example 2, a paste-like positive electrode composite material was prepared by adding and kneading a lithium oxide (positive electrode active material) and an N-methyl-2-pyrrolidone (NMP) solution (KF Polymer, product number: L#1120, manufactured by Kureha Corporation) containing acetylene black (trade name: HS-100, manufactured by Denka Co., Ltd.) and PVDF as a binder in a ratio of positive electrode active material: acetylene black: PVDF to a composition of 85:10:5 (mass ratio). When preparing the positive electrode composite material, the viscosity of the paste was adjusted by adding NMP. The obtained positive electrode composite material was applied to an Al foil with a thickness of 40 μm, which served as a current collector, and then dried in air at 60°C for 1 hour, and then vacuum dried at 150°C for 8 hours, and punched into a circle with a diameter of 14.5 mm, thereby obtaining a positive electrode.
[0147] (2) Fabrication and evaluation of Li half-cells
[0148] A coin-type battery CR2032 type was assembled using the above-mentioned positive electrode, a polyethylene porous film (thickness 16 μm) as a separator, a 1 M LiPF6 solution as a non-aqueous electrolyte (the solvent is a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 30:35:35), and metallic lithium as a counter electrode. It should be noted that the assembly of the battery was carried out in a glove box with an argon atmosphere. Using the produced coin-type battery, a charge and discharge test was carried out under the following conditions at 25°C, in the voltage range of 1.5 to 4.8 V in Examples 1 to 8 and Comparative Examples 1 to 3, and in the voltage range of 1.5 to 4.5 V in Examples 9 and 10. The measurement results of the first discharge energy density and energy conversion efficiency are shown in Table 3.
[0149] Charge and discharge conditions: constant current constant voltage (CC-CV) charging at 30 mA / g and cut-off condition 6 mA / g.
[0150] Discharge conditions: constant current (CC) discharge at 30 mA / g.
[0151] [Table 3]
[0152]
[0153] Figure 4 This is a graph showing the first charge and discharge curves of Comparative Example 1 and Examples 1 and 3 to 6. Figure 5 This is a graph showing the first charge and discharge curves of Comparative Example 1 and Examples 2, 7, and 8. Figure 6 This is a graph showing the first charge and discharge curves of Comparative Example 1 and Examples 9 and 10. Figure 7 Graph showing the first charge and discharge curves of Comparative Examples 1 to 3. Figures 4 to 7In the graph, the horizontal axis represents the capacity of the positive electrode active material, and the vertical axis represents the battery voltage. Figure 8 The composition ratio x of lithium (i.e., the composition formula Li x Mn 1.4 V 0.3 A graph with the x in O4) as the horizontal axis and the battery voltage as the vertical axis. Figure 8 A in the figure represents the state before charging begins. At this time, the composition of the lithium oxide contained in the positive electrode is Li 1.6 Mn 1.4 V 0.3 O4. After that, the above charge and discharge test was carried out to achieve Figure 8 The composition of the lithium-containing oxide at B (discharge completion) is Li. If the amount of lithium ion movement is calculated from the current value, then 2.45 Mn 1.4 V 0.3 O4 has excellent lithium ion embedding ability.
[0154] <Observation using a transmission electron microscope>
[0155] The measurement was carried out under the following conditions.
[0156] Equipment: Analytical electron microscope ARM200F, manufactured by JEOL Ltd.
[0157] Measurement conditions: Acceleration voltage 200 kV
[0158] Sample preparation: The lithium-containing oxide of Example 5 was prepared as a sample by a dry dispersion method in an inert atmosphere.
[0159] Fig. 9 2 shows an electron beam diffraction image of the sample of Example 5. The circle indicated by BF in the figure is the observation position of the bright field image (not shown). Fig. 9 The circles 1, 2, and 3 in the figure represent the insertion positions (openings) of the objective lens diaphragms. Fig. 9 In the image, since multiple bright spots are observed to be arranged in a ring shape and halos are observed, it can be seen that a crystalline phase and an amorphous phase exist.
[0160] Fig.10 This is a diagram showing a dark field observation image of the sample of Example 5 using a transmission microscope. Fig.10 (A), (B) and (C) in Fig. 9 The dark field observation image is obtained by inserting the objective lens aperture into positions 1, 2, and 3 in the image. Fig.10 The white granular structure in the middle represents a crystalline phase, and it can be seen that nanocrystals with a diameter of 2 to 8 nm are dispersed in the sample.
Claims
1. An alkali metal-containing oxide having a spinel structure and having a composition represented by the following general formula (1): In an X-ray diffraction pattern of the alkali metal-containing oxide measured at 25° C. using CuKα radiation, a peak having a half-value width of 0.5 to 5° in terms of 2θ is observed in the range of 40 to 45° in terms of 2θ. A x M’ a M” b Z c O 4-e X d (1) In formula (1), 1.1<x≤2.8, 0.8≤a<1.9, 0.05<b≤0.6, 1.0≤a+b<2.0, 0≤c<0.2, 0≤d<1.0, 0≤e<1.0, A is an alkali metal element, M' is at least one element selected from the group consisting of Ti, Cr, Mn, Fe, Co, Ni and Cu, M" is at least one selected from the group consisting of Si, P, S, Ge and V, Z is an element of Group 2 to Group 16 of the periodic table other than oxygen, M' and M", X is a halogen element.
2. The alkali metal oxide according to claim 1, wherein For the alkali metal oxide, an electrochemical cell is prepared which includes an electrode including the alkali metal oxide, a counter electrode of lithium metal, and an electrolyte solution containing a lithium salt disposed between the electrode and the counter electrode, and Li / Li + When the electrochemical battery is charged to 4.8 V and then discharged to 1.5 V, x in the general formula (1) is in the range of 2.2 to 2.
8.
3. The alkali metal-containing oxide according to claim 1 or 2, wherein In the general formula (1), A contains Li.
4. The alkali metal oxide according to claim 1 or 2, wherein In the general formula (1), M" includes V.
5. The alkali metal-containing oxide according to claim 1 or 2, wherein In the general formula (1), 1.1<x≤2.
0. 6 . An electrode comprising the alkali metal-containing oxide according to claim 1 . 7 . A battery comprising the electrode according to claim 6 as a positive electrode and a negative electrode containing lithium.
8. A positive electrode active material, comprising a composite oxide containing an alkali metal element, an element M' and an element M", wherein: The positive electrode active material contains 8 to 15 mass % of alkali metal elements, 32 to 57 mass % of at least one element M' selected from the group consisting of Ti, Cr, Mn, Fe, Co, Ni and Cu, and 3 to 30 mass % of at least one element M", selected from the group consisting of Si, P, S, Ge and V. In the X-ray diffraction pattern obtained by measuring the positive electrode active material using CuKα rays at 25°C, a peak pattern of a spinel structure originating from the composite oxide was observed, and a peak with a half-value width of 0.5 to 5° was observed in the range of 40 to 45° in 2θ. 9 . The alkali metal-containing oxide according to claim 1 , which has an amorphous phase.
Citation Information
Patent Citations
Non-aqueous secondary battery
JP1995122299A
Lithium manganate composition
JP2000063123A
Multiple metal ion doped oxide cathode materials for lithium secondary batteries and lithium ion secondary batteries
JP2000500280A
Lithium-ion battery
JP2014525667A